1999
DOI: 10.1046/j.1365-2648.1999.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between diabetes knowledge and compliance among Chinese with non‐insulin dependent diabetes mellitus in Hong Kong

Abstract: This study examines the relationship between diabetes knowledge and compliance among Chinese with non-insulin dependent diabetes mellitus (NIDDM) in Hong Kong. A cross-sectional design was used to collect data through structured self-report interviews based on validated scales assessing diabetes knowledge, compliance behaviours and demographic data. The Diabetes Knowledge Scale was used to sample knowledge in the major areas of basic physiology of diabetes and general principles of diabetes care. Compliance le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 24 publications
5
37
1
Order By: Relevance
“…A study done in Egypt also showed a finding similar with the current study that the level of compliance increased with the improvement of the patient’s level of knowledge about diabetes [6, 30]. On the other hand, findings of a study conducted in China indicated that there was no association between the knowledge of diabetes and compliance [31]. Formal diabetes education participation was done by only 23% of the patients.…”
Section: Discussionsupporting
confidence: 84%
“…A study done in Egypt also showed a finding similar with the current study that the level of compliance increased with the improvement of the patient’s level of knowledge about diabetes [6, 30]. On the other hand, findings of a study conducted in China indicated that there was no association between the knowledge of diabetes and compliance [31]. Formal diabetes education participation was done by only 23% of the patients.…”
Section: Discussionsupporting
confidence: 84%
“…Fitzgerald et al, [27] found that the level of adherence increased with the improvement of the patient's level of knowledge. On the other hand, findings of the study conducted in China by Chan et al, [28] indicated that there was no association between the patient′s knowledge and adherence.…”
Section: Discussionmentioning
confidence: 95%
“…In Hong Kong, researchers could not fi nd any association between diabetes knowledge and compliance. They suggested that there was a gap between what the patients were taught and what they were actually doing (Chan and Molassiotis 1999).…”
Section: Patient Knowledgementioning
confidence: 99%